Regional Tax Competition in Canada, the United States and Russia: Assessment of Regulatory Experience - Michael V. Alexeev; Andrey V. Korytin; Elena V. Melkova (Финансовый журнал, 2022)
Recent changes in the Russian tax legislation aimed at weakening the tax powers of the federal subjects in relation to profit tax open the question of a reasonable degree of limitation of the fiscal autonomy of Russian regions, as well as the regulation of regional tax competition. This article discusses the peculiarities of regulation of domestic tax competition in Canada and the United States on the basis of an analysis of the provisions of the tax legislation related to the fiscal powers of regional jurisdictions (provinces, states). The article focuses on approaches to limiting harmful tax practices that affect the economy or budget revenues of other regions. Empirical studies confirm the existence of negative effects of domestic tax competition, as well as the relevance of measures to restrict it. The considered countries make efforts to limit domestic tax competition both at the level of interregional agreements and at the level of central authorities. However, practice shows that it is difficult to ensure actual implementation of agreements at the regional level, so regulation by the central government is of key importance. Based on this result, recommendations are given for taking measures against harmful tax competition between the regions of Russia.